Improving Students’ Reading Comprehension through the Flipped Classroom Model in Senior High School - Aditya Dwi Putra; Ririn Pusparini (SM Institute, 2026)
Reading comprehension is an essential skill in English learning because it enables students to understand, interpret, and evaluate information presented in written texts. However, reading instruction in English classrooms often remains teacher-centred, limiting students’ opportunities to discuss, analyse texts, and construct meaning independently. This study aimed to analyse the effectiveness of the flipped classroom model in improving Grade XI students’ reading comprehension at SMAN 1 Baureno. The study employed a quantitative approach using a quasi-experimental non-equivalent control group design. The sample consisted of 65 students, with 32 students in the experimental group and 33 students in the control group. The research instrument was a reading comprehension test consisting of 20 multiple-choice questions. The data were analysed using descriptive statistics, the Shapiro-Wilk normality test, Levene’s homogeneity test, paired-samples t-test, independent-samples t-test, and Cohen’s d. The results showed that the experimental group’s mean score increased from 81.56 to 88.28, while the control group’s mean score increased from 81.21 to 83.18. The paired-samples t-test for the experimental group showed a significant improvement (p < 0.001), whereas the control group showed no significant improvement (p = 0.125). The independent-samples t-test showed a significant difference in post-test scores (p = 0.004), with a moderate effect size (d = 0.743). These findings indicate that the flipped classroom model effectively improves students’ reading comprehension.